Latviešu valodas stieptās un nestieptās zilbes intonācijas akustiskā realizācija divu intonāciju sistēmas informantu runā - Remerts, Andris (Latvijas Universitāte, 2013)
Šajā darbā ir apskatīta latviešu valodas stieptās un nestieptās zilbes intonācijas akustiskā realizācija divu intonāciju sistēmas informantu runā. Intonācijas ir pētītas minimālajos pāros – heterotonos. Spektrogrammās tika mērīti intonēto garskaņu ilguma, pamattoņa un intensitātes rādītāji. Informantu izrunā visvairāk atšķīrās pamattoņa līknes – stiepti intonētajam garskanim tās biežāk ir līdzenas vai kāpjošas, nestiepti intonētajam – krītošas vai kāpjoši krītošas. No citiem rādītājiem atšķirības konstatētas arī pamattoņa diapazonā (biežāk tas ir lielāks nestiepti intonētajam garskanim), bet relatīvā ilguma atšķirības ir nelielas (biežāk relatīvi ilgāki ir stiepti intonētie garskaņi). Intensitātes rādītājos nav novērotas atšķirības attiecīgi intonēto garskaņu starpā. Atslēgvārdi: heterotoni, zilbes intonācijas, stieptā un nestieptā intonācija.

This master's thesis deals with the acoustic realization of drawn and non-drawn syllable intonations in speech of Latvian speakers using two-tone system. Syllable intonations are analyzed in minimal pairs (so called heterotones). The analysis of spectrograms was based on the description and investigation of attributes of bearers of intonation (long vowels, diphtongs and tautosyllabic vowel junctions with the sonants /l/, /r/, /m/, and /n/) – fundamental frequency, intensity, and relative duration. In the speech of informants the drawn intonation is characterized by level or rising fundamental frequency, non-drawn intonation is characterized by fall or rise and fall of fundamental frequency. In many cases the non-drawn intonation compared to the drawn intonation differs by having a wider range of fundamental frequency. Relative duration differences are small. Syllable intonations do not differ in intensity. Key words: heterotones, syllable intonations, drawn and non-drawn intonation.
Acoustic Realization of Drawn and Non-Drawn Tone in Speech of Informants Using Two-Tone System in Latvian
Keywords: Filoloģija